Etika Berkomunikasi Tertulis dalam Lingkungan Masyarakat - Yuniarsih, Yuniarsih; Mulya, Komara; Ristiawati, Tia; Erra Rismorlita, Cut; Grasia Azmin, Gres (Fakultas Ilmu Budaya Universitas Jenderal Soedirman, 2025)
This community service activity was motivated by the declining quality of written communication in society, especially in digital interactions, which often leads to misunderstandings. The aim of this program is to enhance the knowledge and skills of the community, specifically members of the Family Welfare Program (PKK) in Pulogadung District, regarding the ethics of written communication. The method used was a counseling and workshop approach, with effectiveness measured through a pre-test and post-test design administered to 18 participants. The results showed a significant increase in participants' knowledge, with the average score rising from 31.17 in the pre-test to 41.33 in the post-test. The program's effectiveness was calculated at 60.4%, placing it in the